A note on the Cournot-Bertrand profit differential: A reversal result in a differentiated model with wage bargaining - Rattanasuda Poolsombat; Gianluigi Vernasca (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
We consider an oligopolistic model with product differentiation in which firm's costs are not given exogenously but are the result of a wage bargaining process between firms and local unions. Using a generalised version of the model of Lopez and Naylor (2004) we compare Cournot and Bertrand equilibria. We show that, contrary to standard results that Cournot equilibrium profits always exceed those under Bertrand competition, Bertrand profits can be higher than Cournot profits for some particular values of the parameters of the wage bargaining. This holds even if there are more than two firms in the economy. However, there is a critical level in the number of firms above which, independently on the values of the parameters of the model, the standard result conitnues to hold.
Keywords: 330; Produktdifferenzierung; Oligopol; Tarifverhandlungen; Theorie